Investigating the potential of adding thermal mass to mitigate overheating in a super-insulated low-energy timber house - Rodrigues, Lucélia Taranto; Sougkakis, Vasileios; Gillott, Mark C. (Oxford University Press, 2016)
Evidence suggests that many UK dwellings are subjected to overheating or will be at some point in the future. Dwellings built using modern methods of construction may have a higher overheating risk due to the low levels of thermal mass associated with most of these methods. The Nottingham HOUSE, a prefabricated timber modular building designed to zero-carbon and Passivhaus standards, was examined in terms of overheating occurrence. The ability of a high-density fibreboard and phase change materials to provide additional levels of thermal mass was examined with the results suggesting that these can help regulate internal temperatures with the benefit of being easy to integrate.